Extremely low frequency–electromagnetic fields promote chondrogenic differentiation of adipose-derived mesenchymal stem cells through a conventional genetic program - Lucrezia Zerillo; Concetta Claudia Coletta; Jessica Raffaella Madera; Gabriella Grasso; Angelapia Tutela; Pasquale Vito; Romania Stilo; Tiziana Zotti (Scientific Reports, 2024)
Abstract Progressive cartilage deterioration leads to chronic inflammation and loss of joint function, causing osteoarthritis (OA) and joint disease. Although symptoms vary among individuals, the disease can cause severe pain and permanent disability, and effective therapies are urgently needed. Human Adipose-Derived Stem Cells (ADSCs) may differentiate into chondrocytes and are promising for treating OA. Moreover, recent studies indicate that electromagnetic fields (EMFs) could positively affect the chondrogenic differentiation potential of ADSCs. In this work, we investigated the impact of EMFs with frequencies of 35 Hertz and 58 Hertz, referred to as extremely low frequency-EMFs (ELF–EMFs), on the chondrogenesis of ADSCs, cultured in both monolayer and 3D cell micromasses. ADSC cultures were daily stimulated for 36 min with ELF–EMFs or left unstimulated, and the progression of the differentiation process was evaluated by morphological analysis, extracellular matrix deposition, and gene expression profiling of chondrogenic markers. In both culturing conditions, stimulation with ELF–EMFs did not compromise cell viability but accelerated chondrogenesis by enhancing the secretion and deposition of extracellular matrix components at earlier time points in comparison to unstimulated cells. This study showed that, in an appropriate chondrogenic microenvironment, ELF–EMFs enhance chondrogenic differentiation and may be an important tool for supporting and accelerating the treatment of OA through autologous adipose stem cell therapy.